2016
DOI: 10.3847/0004-6256/152/3/72
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity and Age of the Stellar Stream Around the Disk Galaxy NGC 5907

Abstract: Stellar streams have become central to studies of the interaction histories of nearby galaxies. To characterize the most prominent parts of the stellar stream around the well-known nearby (d=17 Mpc) edge-on disk galaxy NGC 5907, we have obtained and analyzed new, deep gri Subaru/Suprime-Cam and 3.6 μm Spitzer/Infrared Array Camera observations. Combining the near-infrared 3.6 μm data with visible-light images allows us to use a long wavelength baseline to estimate the metallicity and age of the stellar popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 74 publications
2
21
0
Order By: Relevance
“…Their evocative image, whose main features could be reproduced with an N-body model, has taken on an iconic status, serving as a powerful demonstration of the shredding of a small galaxy. 7 Some years later NGC 5907 was also observed by Laine et al (2016), who combined data from the Spitzer Space Telescope with optical Subaru images. These authors studied the part of the stream that was detected by Shang et al (1998) and do not comment on the second loop that was reported by M08.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Their evocative image, whose main features could be reproduced with an N-body model, has taken on an iconic status, serving as a powerful demonstration of the shredding of a small galaxy. 7 Some years later NGC 5907 was also observed by Laine et al (2016), who combined data from the Spitzer Space Telescope with optical Subaru images. These authors studied the part of the stream that was detected by Shang et al (1998) and do not comment on the second loop that was reported by M08.…”
mentioning
confidence: 98%
“…One of the best-known tidal features outside of the Local Group is the stellar stream associated with NGC 5907, an edge-on spiral galaxy with a stellar mass of ≈ 8 × 10 10 M (Laine et al 2016) at a distance of 17 Mpc (Tully, Courtois, & Sorce 2016). The stream was discovered by Shang et al (1998) and Zheng et al (1999), who detected sections of a loop around the disk of NGC 5907 using the Beijing Astronomical Observatory 0.6/0.9 m Schmidt telescope.…”
mentioning
confidence: 99%
“…The pitfalls of deep imaging are illustrated by the recent controversy about the tidal streams of the Splinter Galaxy, NGC 5907. Several amateur observers equipped by small telescopes have observed the streams warping the galaxy multiple times -the refereed example is Martínez-Delgado et al (2008) -while the professional astronomers with bigger telescopes were able to detect only a part of this structure (Laine et al 2016;van Dokkum et al 2019;Müller et al 2019c;Alabi et al 2020). The case remains unresolved.…”
mentioning
confidence: 99%
“…The imaging used for this work was obtained using the wide-field Suprime-Cam imager on the 8.2m Subaru telescope with the SDSS gri filters under photometric conditions (0 .6−0 .9 seeing). Details of the observations and data reduction are explained in Laine et al (2016). The imager has a total field-of-view of 34 ×27 with a pixel scale of 0 .2 per pixel.…”
Section: Observationsmentioning
confidence: 99%
“…In this study, we present wide-field Subaru imaging of NGC 5907 and Keck spectroscopy of several GC candidates. We assume a distance of 17 Mpc to NGC 5907, as adopted by Laine et al (2016) and summarize salient properties of NGC 5907 in Table 1. Many of its properties are similar to those of the Milky Way.…”
Section: Introductionmentioning
confidence: 99%